2019
DOI: 10.1515/nanoph-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic phase modulation and diffraction-limited microfocusing generated by pairs of subwavelength dielectric scatterers

Abstract: Diffractive approaches are needed when refractive microlenses reach their focusing limit at the micron-scale in visible light. Previously, we have reported on micron-sized optical lenses based on the diffraction of metallic nanowires. Here, we extend our study to lenses based on pairs of subwavelength dielectric scatterers. Using simulations by two-dimensional finite element method, we demonstrate that focusing holds for pair spacings as small as the wavelength-size. For pairs with distances between inner wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Recently, it has been shown that two identical rectangular dielectric rods to make a diffraction-limited focus 17 . Based on this results we have proposed and demonstrated a method of generating diffraction-limited PH by breaking the symmetry of these systems based on their individual scattering and diffraction properties through variations of their dimensions and refractive indices 18 .…”
Section: Dual-dielectric Structure For Generating Photonic Hooksmentioning
confidence: 99%
“…Recently, it has been shown that two identical rectangular dielectric rods to make a diffraction-limited focus 17 . Based on this results we have proposed and demonstrated a method of generating diffraction-limited PH by breaking the symmetry of these systems based on their individual scattering and diffraction properties through variations of their dimensions and refractive indices 18 .…”
Section: Dual-dielectric Structure For Generating Photonic Hooksmentioning
confidence: 99%
“…Previously, we have used the two‐photon polymerization of acrylates to demonstrate the fabrication of microlens arrays based on the diffraction of microgrids. [ 50 ] We obtained periods as small as 1.2 µm, that are needed for the continuous trend of downsizing the pixel size of CMOS sensors. [ 51 ] Due to the low refractive index of 1.5, the optimized line widths and heights, for high diffraction efficiency, were 0.4 and 0.8 µm, respectively.…”
Section: Diffractive Optical Nanostructures With High Refractive Inde...mentioning
confidence: 99%
“…
Near-field, sub-wavelength, and localized curved light beams, known as photonic hooks [1]-[3], discovered in 2015 [2], have become an area of interest due to their relatively simple design, compactness and potential to be used in a number of applications such as in sensing and optical trapping [2]. Recently, it has been shown how concepts to design focusing devices in the microwave and optical regimes using mesoscale particles (dimensions in the order of the operational wavelength) [4]-[10] such as two identical rectangular dielectric particles to make a diffraction-limited focus [11] can be exploited to produce photonic hooks by breaking the symmetry of these systems. This asymmetry can be introduced using several techniques such as asymmetric illumination (oblique incidence) or by changing the shape and dimensions of the particle [1].
…”
mentioning
confidence: 99%